From pandemic to podium? Norwegian Olympic handball players` journey to Tokyo 2020 - Aase, E.; Abrahamsen, F. E.; Gustafsson, H. (Frontiers in Psychology, 2025)
Introduction: Mental preparation ahead of the Olympic Games (OGs) has been an area of interest for sports psychology researchers over several decades. However, there are few studies based on athlete perspectives of their experiences coping with pressure at this competition level. The COVID-19 pandemic also placed athletes in a demanding situation as they had to deal with the suspension of sport activity, isolation, and general uncertainty—culminating in the first postponement of the OGs in peacetime. Athletes had to balance coping with everyday life in a pandemic with navigating training in ever-changing conditions, indicating it was particularly valuable to investigate mental preparations ahead of the Tokyo OGs.